Perbandingan Kinerja Profitabilitas Bank BJB Sebelum dan Setelah Menerapkan Mobile Banking - Ris Gabe Jefferson Sihombing; Hasbi Assidiki Mauluddi; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study was conducted with the aim of being able to compare the profitability performance of BJB bank before and after using Mobile Banking. This study uses financial statements 5 years before using Mobile Banking, namely in 2010-2014 and 5 years after using Mobile Banking, namely in 2015-2019. This comparison of profitability performance is reviewed from several aspects that are affected by the use of Mobile Banking in BJB bank services, the affected aspects include: a decrease in Return on Assets (ROA) and Return on Equity (ROE), an increase in Earnings per Share (EPS). The results of the normality test show that all variables are normally distributed so that all variables are tested using the Paired sample t-Test, namely the ratio of Return on Assets (ROA), the ratio of Return on Equity (ROE), and Earning per Share (EPS). The Return on Assets (ROA) ratio has the result that there is a significant difference before and after using Mobile Banking. In the ratio of Return on Equity (ROE) there is no significant difference. While in Earning per Share (EPS) there is a significant difference before and after using Mobile Banking